(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Cryptococcal meningoencephalitis, an invasive fungal infection caused by an encapsulated fungus Cryptococcus neoformans should be suspected in immune compromised individuals with defective cell-mediated immunity and patients on immunosuppressive drugs with recent development of fever, confusion and loss of consciousness. A rapid diagnosis is fundamental for decreasing morbidity and mortality from cryptococcal disease. Cerebrospinal fluid (CSF) study and simple stain like India Ink Stain can be performed for diagnosis of cryptococcal meningoencephalitis. Here, we report a case of cryptococcal meningoencephalitis in chronic lymphocytic leukemia (CLL) patient on immunosuppressive drugs diagnosed by CSF study and India ink stain which responded dramatically with antifungal agents after diagnosis. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 87-89